THE MIDWIFERY CARE OF Mrs. F, IUD ACCEPTOR IN THE WORK AREA OF PEUKAN BADA COMMUNITY HEALTH CENTER, ACEH BESAR, IN 2025 - Sari, Annisa Fatika; Lajuna, Lia; Sriyanti, Cut (Department of Midwifery, Health Polytechnic of Aceh, 2025)
Reproductive health includes physical, mental, and social well-being, which can be achieved through the family planning (KB) program. One of the recommended methods is the Intrauterine Contraceptive Device (IUD) as part of the Long-Term Contraceptive Method (MKJP). At the Pekan Bada Health Center in 2022, out of 1,407 fertile age couples (PUS), 11.9% used IUDs. Midwives play an essential role in increasing the scope of IUD use through promotive, preventive, curative, and rehabilitative services. Based on this, the author conducted this case study as a final assignment report entitled